2016
DOI: 10.1002/14651858.cd005517.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Materials for retrograde filling in root canal therapy

Abstract: Analysis 1.2. Comparison 1 MTA versus IRM, Outcome 2 Success rate-2-year outcome (participants as unit of analysis)............ Analysis 2.1. Comparison 2 MTA versus Super-EBA, Outcome 1 Success rate-1-year outcome (participants as unit of analysis)..... Analysis 3.1. Comparison 3 Super-EBA versus IRM, Outcome 1 Success rate-1-year outcome (teeth as unit of analysis)............. Analysis 4.1. Comparison 4 Dentine-bonded resin composite versus glass ionomer cement, Outcome 1 Success rate-1-year outcome PP anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 66 publications
2
32
0
Order By: Relevance
“…Consequently, the adaptation property of a filling material may not be a significant factor affecting clinical outcome, which implies that other clinical factors exist that contribute to controlling intraradicular infection. A recent systematic review that aimed to clarify the clinical effect and safety of different materials for root‐end filling revealed that more high‐quality randomised controlled trials are required to determine the benefits of any one material over another . As no in vivo study was identified in the present systematic review, clinical studies are necessary to obtain information on the relation between the clinical outcome and the adaptation property of root‐end filling materials.…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, the adaptation property of a filling material may not be a significant factor affecting clinical outcome, which implies that other clinical factors exist that contribute to controlling intraradicular infection. A recent systematic review that aimed to clarify the clinical effect and safety of different materials for root‐end filling revealed that more high‐quality randomised controlled trials are required to determine the benefits of any one material over another . As no in vivo study was identified in the present systematic review, clinical studies are necessary to obtain information on the relation between the clinical outcome and the adaptation property of root‐end filling materials.…”
Section: Discussionmentioning
confidence: 98%
“…The six studies examined five different comparisons, including MTA versus intermediate restorative material (IRM), MTA versus super ethoxybenzoic acid cement (Super‐EBA), Super‐EBA versus IRM, dentine‐bonded resin composite versus glass ionomer cement and glass ionomer cement versus amalgam’ (Ma et al . ). Example 6e : ‘Initially, 109 possibly relevant articles were identified. After screening and full‐text evaluations, 28 articles that met the inclusion criteria were analysed, reporting on a total of 84 patients with altered sensation after extrusion of root canal filling materials’ (Rosen et al .…”
Section: Explanation and Endodontic Examples Of Items In The Prisma Fmentioning
confidence: 97%
“…The six studies examined five different comparisons, including MTA versus intermediate restorative material (IRM), MTA versus super ethoxybenzoic acid cement (Super‐EBA), Super‐EBA versus IRM, dentine‐bonded resin composite versus glass ionomer cement and glass ionomer cement versus amalgam’ (Ma et al . ).…”
Section: Explanation and Endodontic Examples Of Items In The Prisma Fmentioning
confidence: 97%
See 2 more Smart Citations